POLA AGIHAN DAN INTENSITAS PENYAKIT BUSUK PANGKAL BATANG LADA DI PROVINSI SULAWESI TENGGARA - BANDE, LA ODE SANTIAJI; HADISUTRISNO, BAMBANG; SOMOWIYARJO, SUSAMTO (Jurnal Agroteknos, 2014)
The success of foot rot disease control is largely dependent on information data of pepper cultivation conditions, distribution pattern of the disease, and the magnitude of the intensity of the disease. This study aimed to determine the condition of pepper cultivation, distribution pattern of pepper foot rot disease, the development of disease symptoms, and intensity of pepper foot rot disease in Southeast Sulawesi. Data cultivation conditions, distribution of the disease, progression of symptoms, and the intensity of the disease were obtained by means of surveys in pepper plantations and interviews with pepper farmers. The results showed that the pepper plantations in Southeast Sulawesi were cultivated on flat to hilly topography, and the cultivation method was very conventional but herbicide use was very intensive. The development of wilt symptoms on pepper plants was very quick in dry weather but slow in the wet. Pepper foot rot disease has patch distribution. The highest intensity of the pepper foot rot disease was in less weedy plantations with intensive use of herbicides. The intensity of the pepper foot rot disease in Southeast Sulawesi was 61,2% with the spread in each district namely South Konawe at 53,8%, Konawe at 63,7% and Kolaka by 61,2%.